Investigation of Borehole Stability in Malmberget - Ghosh, Rajib (2012)
Sublevel caving method is generally selected for large ore bodies with steep slope. This method is based on the gravity flow of the ore to get better recovery. Due to the continuous caving as the mining goes deeper, fractures of hanging wall occur consequently and thus it collapses into the cave. The local stress field is also affected by various mining activities and it initiates the movement of geological structures in the rock mass and causes seismic event frequently. Thus, it is required to investigate instability problems in various ore bodies in the mine as mining advances deeper and deeper. Investigation of boreholes by filming is a technical way to inspect the overall stability in an ore body.This project work mainly consists of three parts such as Pre-investigation based on production measurement by collecting data from GIRON (Internal production database in LKAB), Field work by filming and Analysis of the data collected from the field. Three ore bodies named Alliansen, Fabian and Vi-Ri were selected for this work.In the pre-investigation, different problems in the borehole are categorized such as re-drilling, wet holes, stones and concrete in the boreholes in different sublevels where the production was completed or about to complete. Re-drilling maps are drawn in different ore bodies as well. The mine co-ordinates of the ring have been used to locate the approximate area of re-drilling. This pre-investigation enabled us to know which areas in the sublevels are more prone to instabilities in different ore bodies. Thus, drifts were selected around this area in the next sublevels or in the same level for filming. These drifts are classified into three criteria; ongoing production, open cut is finished and open cut has not been done.In Alliansen, level 992 m and 1022 m have been selected for field work. In addition, level 855m and 880 m in Fabian and 1026 m in Vi-Ri are investigated by filming. It was not possible to get sufficient filming from the level 880 m in Fabian and 1022 m in Alliansen due to the ...